The principal's leadership role in a successful rural school in Namibia - Kawana, Joseph Jost (Rhodes University, Faculty of Education, Department of Education, 2007)
Rural schools generally find it hard to function effectively for a variety of reasons, and managing and leading these schools brings additional challenges. This study explored the role of the principal in an academically successful rural school in Namibia. It drew on leadership theory and findings from related studies to make sense of this particular case of leadership against the odds. Using the interpretive orientation, the research explored selected organisation members' perceptions of the principal's leadership through semi-structured interviews. The study found that the actions and attitudes of the leader had a significant influence on the school's performance. The manner in which the principal conducted himself, the shared vision he encouraged and his insistence on associating with all stakeholders involved in education, were instrumental in the organization's positive achievements. The principal was shown as committed and a leader with good interpersonal working relationships. The study also revealed that this principal was both a person- and taskoriented leader, and closely resembled the ideals of transformational leadership. This study further found that, through the principal's instructional leadership, teaching and learning are seen as the core of the school's activities. Finally, the principal's leadership role opens the school to the community and results in strong and mutually beneficial relationships between the school and its community.
Keywords: Rural schools -- Namibia; School principals -- Namibia; Educational leadership -- Namibia; School management and organization -- Namibia